Standardization and optimization of salt concentration of brine used in the production of pickled green mangoes - Uy, Darryl L. (College of Home Economics, University of the Philippines Diliman, 2014)
Katchamita mangoes were utilized in the production of green mango pickles in order to standardize the salt concentration of the brine used to ferment the product. Varying salt concentrations (10%, 12%, 15%, and 20%) were used to ferment the mango slices for five days. The physico-chemical attributes of the brine before and after fermentation were explored. Results show that the salinity of the brine decreased after fermentation occurred, while the pH of the brine increased after fermentation. The largest decrease in salinity occurred to the brine with 20% salt concentration, with a drop from a salinity of 14.5 to 12.5 after fermentation. The largest increase in pH occurred to the brine with 15% salt concentration, with a rise in pH from 1.45 to 3.10. The physico-chemical attributes of the fermented mangoes were studied as well, and significant differences were observed between the pickles produced from the varying brine treatments. Regression analysis showed a quadratic relationship existing between the color (lightness, redness, and yellowness), water activity and titratable acidity of the pickled mangoes and varying brine treatments. On the other hand, the pH of the pickled mangoes was shown to have a quadratic relationship with the varying brine treatments. Pickles from the brine with 10% salt content had the highest mean yellowness value of 89.45, highest mean lightness values of 71.45, and lowest mean redness value of 7.81. Meanwhile pH and water activity of the pickles were optimum at the 20% salt concentration with mean values of 2.96 and 0.90, respectively. Conversely, the mean titratable acidity values of all brine treatments were not within the optimum range of titratable acidity of pickled mangoes. Lastly, consumer acceptance of the product was determined using 50 untrained panelist. Results showed that the varying salt concentrations of the brine had no significant effect on the acceptability of the organoleptic qualities of the green mango pickles. It was concluded that brine with any concentration of salt between 10% and 20% is sufficient in producing the green mango pickles due to the insignificant effect of the varying salt content on the organoleptic qualities of the pickles.